Saṅgīta Rūstama-Soharāba : Śāhanāmā uparathī taiyāra kidhelāṃ dāstāna sāthe - Kābarājī, Kekhuśaro Navarojajī, 1842-1904 (Strībodha Ôphisa, 1906)
Libretto, with musical letter notation; based on Firdawsī's Shahnama.